DreamJobs 2007. - Goldstein, Harry (IEEE spectrum)
This paper describes the occupation of 10 technologists that many consider to be dream jobs. The 10 jobs considered cover a wide range of scientific and engineering disciplines including forensic engineering, paleontology, artificial intelligence, and electric vehicle design